Through-thickness microstructure and mechanical properties of electron beam welded 20 mm thick AISI 316L austenitic stainless steel. (15th September 2017) - Alali, M.; Todd, I.; Wynne, B.P.
Abstract: Through thickness microstructure and mechanical properties of defect-free electron beam welded 20 mm thick AISI 316L austenitic stainless steel are investigated as a function of beam power. The weld microstructure characterised by columnar and equiaxed dendritic ferrite in an austenite matrix. The dendritic structure was finer at the bottom of the weld zone. A microstructural boundary called "Parting" was seen along the weld centreline. Tensile tests, using digital image correlation technique, demonstrated that the highest strain concentrated in the FZ. The bottom section of the weld metal showed yield strength of about 14–52 MPa higher than the top section. The ultimate tensile strength in the bottom of the weld was also about 4% higher than the top. The final fracture was detected in the parting region. It was observed from the EBSD scan that the grains in the weld zone contained a weak orientation and showed high Schmid factor intensity with interception between some strong grains and soft grains at the weld centerline boundary. This explains the high weld ductility and the failure to happen in the parting region. Graphical abstract: Highlights: High weld thickness underwent different thermal gradient and growth rate that produced different microstructure and morphologies through the weld. A clear boundary was found at the middle of the fusion zone ("parting" region), which is the weakest part of the weld. The fusion zone was softer than the HAZ and the base metal. The tensile strength test samples ruptured at the centre of the fusion zone, usually in the parting region. However, finer microstructure at the lower parts of the weld enhanced YS and UTS. The grains in the FZ contained weak orientation and showed high Schmid factor intensity with interception between some strong grains and soft grains at the weld centerline boundary. Thus, the failure happened at this region.